2009
DOI: 10.1097/bsd.0b013e3181761528
|View full text |Cite
|
Sign up to set email alerts
|

Extraforaminal Lumbar Interbody Fusion for the Treatment of Isthmic Spondylolisthesis

Abstract: ELIF technique makes exposing only the exiting nerve root easy to perform interbody fusion without violating either the abdominal cavity or the posterior musculoligamentous and the bony stabilizers of the spine. This may be considered as one of the minimally invasive surgical options for isthmic spondylolisthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Commonly employed procedures include anterior lumbar interbody fusion (ALIF), posterior lumbar fusion (PLF), posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF), or a combination of these and other minimally invasive techniques. 25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Data obtained from outcome studies do not support 1 method over another and each technique has its associated complications. 28,[42][43][44][45][46][47][48][49][50] Most of the published literature is retrospective with no standardization of either outcome measures or process measures.…”
Section: Discussionmentioning
confidence: 67%
“…Commonly employed procedures include anterior lumbar interbody fusion (ALIF), posterior lumbar fusion (PLF), posterior lumbar interbody fusion (PLIF), transforaminal lumbar interbody fusion (TLIF), or a combination of these and other minimally invasive techniques. 25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Data obtained from outcome studies do not support 1 method over another and each technique has its associated complications. 28,[42][43][44][45][46][47][48][49][50] Most of the published literature is retrospective with no standardization of either outcome measures or process measures.…”
Section: Discussionmentioning
confidence: 67%
“…Kim et al [16] stated that hypertrophic facet joint with ligamentum flavum thickening may limit the actual dimensions of the safe working zone. Finally, regarding the visceral structures in this area, Baek and Lee [10] reported that extraforaminal ligaments, transforaminal ligaments and foraminal ligamentum flavum could cause tethering of the exiting nerve root and cause of an obstacle in operating on the exiting nerve root. Due to these problems, Kim et al [16] suggested close monitoring and assessment of the pain response to inserted instruments and reviewing the imaging studies of the patients preoperatively to identify any congenital anomaly in the nerve root distorting the normal anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The actual working zone is trapezoid shaped which correlates with the intervertebral disc (IVD) space area [9]. Nowadays, there are many minimally invasive procedures performed by accessing the IVD directly [10]. However, there is a risk of nerve root injury with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The access to the intertransverse space is obstructed by the lateral part of the superior articular process of S1 and the medial portion of the sacral ala. ELIF was therefore considered not to be suitable at the L5-S1 level. 9,10 We propose a technique that makes ELIF surgery at the L5-S1 level feasible. The removal of a 2-to Unilateral foraminal stenosis and concomitant segmental instability 3-cm portion of the medial part of the sacral ala opened the working corridor to uncover the intervertebral disk from the lateral aspect of the spinal canal and to insert interbody fusion grafts without creating instability.…”
Section: Discussionmentioning
confidence: 99%